A critical review on tablet disintegration. (17th August 2016) - Quodbach, Julian; Kleinebudde, Peter
Abstract: Context : Tablet disintegration is an important factor for drug release and can be modified with excipients called tablet disintegrants. Tablet disintegrants act via different mechanisms and the efficacy of these excipients is influenced by various factors. Objective : In this review, the existing literature on tablet disintegration is critically reviewed. Potential disintegration mechanisms, as well as impact factors on the disintegration process will be discussed based on experimental evidence. Methods : Search terms for Scopus and Web of Science included "tablet disintegration", "mechanism tablet disintegration", "superdisintegrants", "disintegrants", "swelling force", "disintegration force", "disintegration mechanisms", as well as brand names of commonly applied superdisintegrants. References of identified papers were screened as well. Results : Experimental data supports swelling and shape recovery as main mechanisms of action of disintegrants. Other tablet excipients and different manufacturing techniques greatly influence the disintegration process. Conclusion : The use of different excipients, experimental setups and manufacturing techniques, as well as the demand for original research led to a distinct patchwork of knowledge. Broader, more systematic approaches are necessary not only to structure the past but also future findings.